Hydrothermal synthesis and photocatalytic performance of Bi2WO6/ZnO heterojunction photocatalysts - Yu, C.; Yang, K.; Yu, J.; Cao, F.; Li, Xin Yong; Zhou, X. (2011)
A series of Bi2WO6/ZnO heterojunction photocatalysts with different Bi2WO6 concentrations (1wt%, 2wt%, 4wt%, 8wt%) were prepared by hydrothermal method at different temperatures(120°C -220°C ). The prepared pure ZnO, Bi2WO6 and Bi2WO6/ZnO heterojunction photocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), Fourier transform infrared spectroscope (FT-IR), UV-Vis diffuse reflectance spectra, and photoluminescence (PL) spectroscope, respectively. The photocatalytic activity of the prepared catalysts was evaluated by photocatalytic degradation of acid orange II under UV light (?=365nm) irradiation. Results show that the photocatalytic activity of Bi2WO6/ZnO heterojunction photocatalysts is superior to that of pure ZnO and Bi2WO6. The optimal concentration of Bi2WO6 is 4wt% and the best hydrothermal temperature is 150°C . Under the above conditions, the prepared composite catalyst shows about 2.4 times in activity of the pure ZnO. The formation of Bi2WO6/ZnO heterojunction could effectively suppress the recombination of the photo generated electron and hole pairs and result in an increase in photocatalytic activity. Moreover, more surface OH groups over the Bi2WO6/ZnO heterojunction photocatalysts will further benefit the improvement of photocatalytic activity.